2013
DOI: 10.1080/10942912.2011.584257
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of the Essential Oil and Oleoresin ofZingiber OfficinaleRoscoe as Affected by Chemical Environment

Abstract: Three different biochemical test systems were chosen based on their solubility to study the antioxidant activity of ginger extracts. Reducing power and DPPH . scavenging activity tests were considered to produce hydrophilic environments and the H 2 O 2 test was considered as creating a lipophilic environment. The average yields were 10.23 ± 1.02% and 0.48 ± 0.19% for oleoresin and essential oil, respectively. The content of total phenols was 67.6 ± 1.08 mg GAE/g of dry extract. In terms of EC 50 , in hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
1
14
1
2
Order By: Relevance
“…These activities can be attributed to the high content in monoterpene hydrocarbons and oxygenated monoterpenes in the essential oil [54]. Additionally, ginger is one of the most widely used herbs that contains several interesting bioactive constituents and possesses health promoting properties [55,56,57]. Previous results have shown the antioxidant activities of ginger essential oil and their bioactive components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities can be attributed to the high content in monoterpene hydrocarbons and oxygenated monoterpenes in the essential oil [54]. Additionally, ginger is one of the most widely used herbs that contains several interesting bioactive constituents and possesses health promoting properties [55,56,57]. Previous results have shown the antioxidant activities of ginger essential oil and their bioactive components.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that compounds such as α-pinene, α-terpineol and geraniol, present at low concentrations in the zinger essential oil, affected the overall efficiency of the antibacterial activity of the oil, indicating a synergistic effect of all components. Using the incorporation method, Bellik and co-workers reported that the MICs values of ginger essential oil ranged from 8.69 mg/mL for S. aureus , 86.92 mg/mL for B. subtilis and 173.84 mg/mL for E. coli strains [57].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant evaluation of Chinese ginger essential oil had EC 50 (mg/ml) of 63.23, 11.68 and 0.118 in reducing power, DPPH scavenging and H 2 O 2 scavenging assays. The corresponding EC 50 for ascorbic acid were 0,.025, 0.005, 0.478, respectively and for quercetin were 0.017, 0.002, 0.078 [35]. Ginger essential oil also showed antioxidant activity in ABST assay.…”
Section: Antioxidant Activity Of Ginger Essential Oilmentioning
confidence: 91%
“…The most important benefit of antioxidants is their ability to fight the accumulation of harmful free radicals in the body. Ginger essential oil protect the cells from these extracellular deleterious radicals, by increasing the liver antioxidant enzyme [26]. All major active ingredients of Ginger, such as zingerone, gingerdiol, zingibrene, gingerols and shogaols, are known to possess anti-oxidant activities [27].…”
Section: Antioxidant Activitymentioning
confidence: 99%